English language needs of engineering undergraduates of an Afghan University - Qasemi, Ahmad Shah (2016)
The current study was conducted to investigate the English language needs of engineering undergraduates at engineering faculties of Jawzjan University. A survey questionnaire and an open-ended interview were used as data collection methods in this investigation. Survey questionnaire was administered to 212 engineering students from three engineering faculties of Jawzjan University to investigate their English language needs and their perceptions regarding the current English language program. In order to get a comprehensive and detailed response to the research questions, an open-ended interview was also administered to identify the perceptions of graduates of the engineering programs, currently employed as engineers regarding the English language program they have studied at Jawzjan University. The findings of the study indicated that English is used extensively at the workplace and plays a significant role in engineering field. The students have good attitudes towards learning English and they study English for academic purpose and their future career. Moreover, the engineering graduates reported that the English instructors need a set of specific skills and competences to teach effectively. They proposed to give more importance to speaking and listening skills. Finally, it was concluded that the current English language program did not match the students’ professional needs. And the given time was not enough to enable the students to achieve the required level of English language proficiency. An investigation of academic English language needs of students through the perceptions of English instructors may provide a comprehensive source for curriculum renewal projects in the future.